Therapy of resistant hypertension in patients with chronic kidney disease complications of anemia in hemodialysis: a case report - Yenry Sumarlim; Emilia Gan; Desantika Wuryana; M. Hari Pristantiningtyas; Herya Putra Dharma; Muhammad Muchlis; Jainuri Erik Pratama; Adji Prayitno Setiadi; Marisca Evalina Gondokesumo (Jurnal Teknologi Laboratorium)
Chronic Kidney Disease (CKD) is closely related to hypertension. Increasing the severity of CKD is associated with more difficult blood pressure control. Appropriate therapeutic management is needed to prevent complications due to uncontrolled hypertension. We report the case of a 78-year-old female patient with a diagnosis of hypertension and end-stage CKD with a history of undergoing hemodialysis for 4 years. The patient has been taking antihypertensive drugs such as Angiotensin Receptor Blockers, Calcium Channel Blockers and Diuretics. However, the administration of three antihypertensive drugs still could not help achieve the expected blood pressure target where the systolic blood pressure was still above 160 mmHg. The patient also has anemia as a common complication of chronic kidney disease. Appropriate management of therapy with fourth-line therapy and hemoglobin repair is necessary to achieve improved clinical outcomes and reduce renal worsening.